Diversidade, riqueza e composição dos gêneros Aspergillus e Penicillium de solos do Quadrilátero Ferrífero - Pereira, Vanessa Maria (2016)
Brazil has the largest global diversity index, however we have witnessed the high percentage of environmental devastation. Maintaining species in the laboratory, together with innovation, are the best alternative to maintai n that diversity. The soil is considered to be a mosaic of micro-habitats, due to its heterogeneity and complexity, and thus is a major ecosystems for the development of microbial populations. This microflora, fungi represent a large part of the biomass, and are of great importance. Aspergillus and Penicillium are the most important genera of fungi related human activities and the exclusive study of these in the soil is unusual. This study evaluated the diversity of fungi Aspergillus and Penicillium isolated from soil of five distinct areas in the Iron Quadrangle, and evaluated its potential toxigenic and correlations with soil nutrients. Twenty soil samples were collected, and for each of these samples, serial dilutions were made in DG18 and DRBC means. The species of Penicillium and Aspergillus were identified by morphological characteristics. The characterization of the unidentified isolates was performed using microscopy and the colonies pictures, as well as phylogenetic study of some of them. The production ocrotoxina A (OTA), citrinin and aflatoxins B1, B2, G1 and G2 was assessed by Thin Layer Chromatography. Diversity, richness and composition of species, and their relationship with soil properties was verified. They were isolated in 1984 specimens belonging to 88 different morphotypes, 50 of these unidentified. An isolate of A. ochraceoroseus been identified and may be the only specimen found outside the Ivory Coast. Phylogenetic analysis of unidentified morphotypes was inconclusive, requiring more genes to confirm the species. All isolates of A. carbonarius produced OTA; any isolated from A. niger and A. niger aggregate OTA produced; all isolates of A. flavus and A. parasiticus produced the respective aflatoxins. All P. citrinum produced citrinin, together with Penicillium sp. 04, 19 and 27. Luminescent several unidentified substances were produced by unidentified morphotypes, which can help identify these and can be compounds of industrial interest. The areas were heterogeneous in diversity, richness and species composition. Grass and Eucalyptus were more representative in richness and abundance of species. Some soil attributes were highly associated with the occurrence and abundance of species of Aspergillus and Penicillium in soils. The species evaluated in this work, are possibly resistant Fe, Mn, Cu, Al and S and can presumably be used in bioremediation of contaminated sites.